Lung Inflammation Induced by Inactivated SARS-CoV-2 in C57BL/6 Female Mice Is Controlled by Intranasal Instillation of Vitamin D - Fernandes de Souza, William Danilo [UNESP]; Zorzella-Pezavento, Sofia Fernanda Gonçalves [UNESP]; Ayupe, Marina Caçador; Salgado, Caio Loureiro; Oliveira, Bernardo de Castro; Moreira, Francielly; da Silva, Guilherme William; Muraro, Stefanie Primon; de Souza, Gabriela Fabiano; Proença-Módena, José Luiz; Araujo Junior, Joao Pessoa [UNESP]; Fonseca, Denise Morais da; et al. (MDPI, 2023)
The COVID-19 pandemic was triggered by the coronavirus SARS-CoV-2, whose peak occurred in the years 2020 and 2021. The main target of this virus is the lung, and the infection is associated with an accentuated inflammatory process involving mainly the innate arm of the immune system. Here, we described the induction of a pulmonary inflammatory process triggered by the intranasal (IN) instillation of UV-inactivated SARS-CoV-2 in C57BL/6 female mice, and then the evaluation of the ability of vitamin D (VitD) to control this process. The assays used to estimate the severity of lung involvement included the total and differential number of cells in the bronchoalveolar lavage fluid (BALF), histopathological analysis, quantification of T cell subsets, and inflammatory mediators by RT-PCR, cytokine quantification in lung homogenates, and flow cytometric analysis of cells recovered from lung parenchyma. The IN instillation of inactivated SARS-CoV-2 triggered a pulmonary inflammatory process, consisting of various cell types and mediators, resembling the typical inflammation found in transgenic mice infected with SARS-CoV-2. This inflammatory process was significantly decreased by the IN delivery of VitD, but not by its IP administration, suggesting that this hormone could have a therapeutic potential in COVID-19 if locally applied. To our knowledge, the local delivery of VitD to downmodulate lung inflammation in COVID-19 is an original proposition.
Keywords: COVID-19; inflammation; lung; mice; SARS-CoV-2; vitamin D